Trust & betrayal in the workplace : building effective relationships in your organization - Reina, Dennis S., 1950- (Berrett-Koehler, 2006)
In competitive global economy, organisations sometimes must make difficult or even painful changes. This title is about trust - the power when it exists, the problems when it doesn't, the pain when it is betrayed and what you can do to restore it. It provides an approach to trust that outlines a common language to discuss trust constructively.